PERANAN ORANG TUA DALAM MENINGKATKAN PRESTASI BELAJAR ANAK DI SEKOLAH ( Suatu Tinjauan Psikologis ) - Nasution, Sahadir (IAIN Padangsidimpuan, 2013)
In learning experience of children at home, of cource the role of parents is very crucial as a leader,Â educator, and motivator. In this cntexct, parents must be motivated, and controlled ad activities of children in order to gain the effective learning in any time. This article presented to describe to become the effective parents.